A study on large bubble motion and liquid film in vertical pipes and inclined narrow channels. (October 2015) - Behafarid, F.; Jansen, K.E.; Podowski, M.Z.
Highlights: New computational model was introduced for large bubbles moving in narrow conduits. Different conduit geometries and orientations were studied. The numerical model was verified for Taylor bubbles in vertical pipes. New model predictions were compared with experimental results for inclined channels. Lubrication effect on bubble velocity along inclined narrow channels was discussed. Abstract: The objective of this paper is to discuss the results of a combined physical and computational analysis of the dynamics of large deformable bubbles in conduits of different geometries and orientations. The situations analyzed included a vertical circular pipe and a narrow rectangular channel of different inclination angles. Three-dimensional simulations were performed at a DNS-scale using the PHASTA code combined with the level set method for interface tracking. The results of computer simulations for Taylor bubble flow in a vertical pipe have been verified against a simplified theoretical model and validated against available general evidence deduced from various experimental studies. The predictions for bubbles flowing along inclined rectangular channels have been validated against experimental data. Several modeling and numerical issues have been investigated, including the effect of a liquid microfilm between the bubble and the wall above it, and the impact of the blending region arising from the level-set model formulation on the accuracy of results.